Exploring spatial vulnerability: inequality and agency formulations in social space. Issue 3 (12th February 2016) - Saatcioglu, Bige; Corus, Canan
Abstract: The authors derive from critical urban geography and consumer research on vulnerability to investigate the ways in which vulnerability within social space is shaped and negotiated. Multiple power dynamics and ideological tension around the production and consumption of social space are explored through diverse examples within the contexts of spaces of consumption, public space as shared good and digital space. The authors offer a conceptualisation of spatial vulnerability and a framework to understand, critique and transform socio-spatial disadvantages. The spatial perspective offered in this article illuminates the ways in which marketplace vulnerability can be institutionalised and become pervasive through and within spaces of everyday life. Yet, the creative and radical potential of social space in managing spatial disadvantages is also explored along with theoretical, managerial, public policy and practical implications.